Dark Septate Endophytes Isolated From Wild Licorice Roots Grown in the Desert Regions of Northwest China Enhance the Growth of Host Plants Under Water Deficit Stress - He, Chao; Wang, Wenquan; Hou, Junling; Li, Xianen (Frontiers in Microbiology, 2021)
This study aimed to explore dark septate endophytes (DSE) that may improve the cultivation of medicinal plants in arid ecosystem. We isolated and identified eight DSE species (Acremonium nepalense, Acrocalymma vagum, Alternaria chartarum, Alternaria chlamydospora, Alternaria longissima, Darksidea alpha, Paraphoma chrysanthemicola and Preussia terricola) colonizing the roots of wild licorice (Glycyrrhiza uralensis) in the desert areas of northwest China. Moreover, we investigated the osmotic stress tolerance of the DSE using pure culture, along with the performance of licorice plants inoculated with the DSE under drought stress in a growth chamber, respectively. Here, five species were first reported in desert habitats. The osmotic-stress tolerance of DSE species was highly variable, A. chlamydospora and P. terricola increased the total biomass and root biomass of host plant. All DSE except A. vagum and P. chrysanthemicola increased the glycyrrhizic acid content; All DSE except A. chartarum increased the glycyrrhizin content under drought stress. DSE × watering regimen improved the glycyrrhizic acid content, and soil organic matter and available nitrogen. Structural equation model analysis showed that DSE × watering regimen positively affected soil organic matter, and total biomass, root length, glycyrrhizic acid and glycyrrhizin (Shapotou site); and positively affected soil organic matter, available phosphorus, and glycyrrhizin (Minqin site); and positively affected the root length (Anxi site). DSE from the Shapotou accounted for 8.0 %, 13.0 % and 11.3 % of the variations in total biomass, root biomass and active ingredient content; DSE from the Minqin accounted for 6.6 % and 8.3 % of the variations in total biomass and root biomass; DSE from the Anxi accounted for 4.2 % and 10.7 % of the variations in total biomass and root biomass. DSE × watering regimen displayed a general synergistic effect on plant growth and active ingredient contents. These findings suggested that the DSE–plant interactions were affected by both DSE species and DSE originating habitats. As A. chlamydospora and P. terricola positively affected the total biomass, root biomass and active ingredient content of host plants under drought stress, they may have important uses as promoters for the cultivation of licorice in dryland agriculture.